Lemahnya Karakter Anak Bangsa di Era Globalisasi - Sukari, Sukari; Hasanah, Amalia (Lembaga Yasin AlSys, 2024)
Character education is something that important to be instilled in the nation's successors so that they can be intelligent in thinking, appreciation in the form of attitudes, and experience of their identity. in thinking, appreciation in the form of attitudes, and experience of their identity, manifested in interactions with God, self, others and the environment. environment. The purpose of this paper is to find out the causes of weakening the character of character in Indonesia and the efforts that can be made to strengthen character education in schools. character education in schools. The research method used in this study uses library research method, which is research based on processed manuscripts (manuscript study), facts and primary and secondary data (supporting data) related to the research focus. with the focus of the research. The results of this study show that the causes of the weakening of the character of students in Indonesia consists of several factors, namely the factors of parents, schools, society and society. from parents, schools, society and social media. The efforts to strengthen character education in schools can be done with four forms of integration, namely integration in subjects, integration through subjects, integration through P5 learning, integration through habituation, and integration through extracurricular activities. and integration through extracurricular activities.